Analysis of the Influence of Competence, Psychological Empowerment, and Organizational Resilience on the Performance of Tunas Honda Pramuka Employees with Psychological Capital as a Mediating Variable - Nabila; Febrianty; Ayu Nursari (Asia Pacific Journal of Business Economics and Technology, 2026)
This study aims to analyze the effect of competence, psychological empowerment, and organizational resilience on employee performance at Tunas Honda Pramuka, with psychological capital as a mediating variable. Previous studies have widely examined employee performance from the perspectives of competence, empowerment, and organizational support; however, limited research has integrated these factors with psychological capital in the context of automotive dealership employees. This study used a quantitative explanatory approach. Primary data were collected through questionnaires distributed to 100 employees of Tunas Honda Pramuka using a saturated sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that competence, psychological empowerment, and organizational resilience do not have a positive and significant direct effect on employee performance. Psychological capital also does not mediate the relationship between competence and employee performance. However, psychological capital mediates the relationship between psychological empowerment and employee performance, as well as organizational resilience and employee performance. In addition, psychological capital has a positive and significant effect on employee performance. This study contributes to human resource management literature by emphasizing psychological capital as a key internal resource for improving employee performance in automotive service organizations.